A promising anode material for sodium-ion battery with high capacity and high diffusion ability: graphyne and graphdiyne. Issue 30 (8th March 2016) - Xu, Zhenming; Lv, Xiaojun; Li, Jie; Chen, Jiangan; Liu, Qingsheng
Abstract : First-principles calculations indicate that a novel atomic hollow structure of graphyne and graphdiyne made up of sp- and sp 2 -hybridized carbon atoms reinforces not only the Na storage capacity but also the Na diffusion. Abstract : An investigation of the energetics and dynamics properties of sodium adsorption on graphyne and graphdiyne has been carried out by first-principles calculations. Graphyne (GY) and graphdiyne (GDY) is the single atomic layer structure of carbon six-member rings connected by one and two acetylenic linkages, respectively. Our calculated results indicate that a novel atomic hollow structure of graphyne and graphdiyne made up of sp- and sp 2 -hybridized carbon atoms reinforces not only the Na storage capacity but also the Na diffusion. For GY and GDY, the maximum sodium storage concentration is NaC4 and NaC3, respectively, far exceeding the upper limit of Na insertion into graphite to form the stage-II compound NaC12 and being also superior to the case of Li inserting into graphite to form LiC6 . By only overcoming a smaller energy barrier of about 0.4 eV, Na ions can easily achieve two-dimensional diffusion on GY and GDY plane. Excellent performances of the sodium storage capacity and sodium diffusion ability make graphyne and graphdiyne promising candidates for the anode material used in sodium-ion batteries.